A Cross-sectional study of cutaneous manifestations in overweight and obese children - Ann Willie Thomas; Anuradha Bhatia; Monika Sharma (Wolters Kluwer Medknow Publications, 2024)
Background: Overweight and obesity are a major public health problem and are now considered to be a global epidemic. The skin is one of the main organs to be affected due to metabolic abnormalities in obesity. The various cutaneous manifestations of obesity are directly related to the age of onset, duration, and severity of the underlying disease. Aims: The aim of this study is to determine the frequency and pattern of cutaneous manifestations in overweight and obese children. Materials and Methods: The present study was a cross-sectional study conducted among 150 overweight and obese children (according to the World Health Organization definition), of age group 5-19 years (school-going children) attending the dermatology and pediatrics outpatient department. The study utilized a prestructured pro forma to record demographic profile, weight, height, and body mass index; the different cutaneous manifestations were noted in overweight and obese children. Relevant investigations such as pus culture, potassium hydroxide (KOH) preparation, and skin biopsy were done wherever indicated. Results: Most of the patients were overweight (82%). Males (61.33%) outnumbered females (38.67%) in our study. Majority of the patients had acanthosis nigricans (74.67%), followed by striae distensae (32.67%), acne vulgaris (20%), and dermatophytosis (17.33%). Hidradenitis suppurativa was found in two children, and cellulite in one child. Conclusion: As obesity and its effects on the skin in school-going children are understudied by dermatologists and pediatricians, a proper examination and diagnosis of different cutaneous manifestations of obesity in children will further help in preventing multiple comorbidities in future.